Frontispiece: The Dynamics of Chemical Reactions: Atomistic Visualizations of Organic Reactions, and Homage to van 't Hoff. Issue 16 (15th March 2018) - Yang, Zhongyue; Houk, K. N.
Abstract : van 't Hoff was awarded the first Nobel Prize in Chemistry in 1901 for the discovery of the laws of chemical dynamics. The study of chemical dynamics has been advanced by the development of molecular dynamics simulations and QM/MM calculations. In the first of a series entitled The Nobel Legacy, van 't Hoff's achievements and their influence on modern chemistry are reviewed. For more details, see the Minireview by K. N. Houk and Z. Yang onpage 3916 ff.